Culture-Led Regeneration and Creative Tourism Development in Indonesia's City Slums: Some Findings from Tangerang City - Forina Lestari; Anna Karenina; Anthony P Nasution (Universitas Pendidikan Ganesha, 2023)
Tourism has been in the spotlight recently, especially in urban slum areas. Many studies have reviewed slum areas. However, transforming slums into creative tourism villages or kampungs is a new phenomenon that emerged in urban slums in Indonesia. Creative kampung, in particular, is a form of tourism that changes the slum area into a tourist destination. This study aims to explore the extent of the creative tourism kampung's sustainability and the role of stakeholders in ensuring the sustainability of this creative tourism village. This study employs descriptive analysis by combining in-depth interviews and literature analysis to unravel creative kampung in practice. This study found that the kampungs' transformation can be seen in physical, social, and environmental dimensions. Moreover, this study also outlines an appropriate strategy to ensure the sustainability of creative kampung. Stakeholders' collaboration to maintain social capital and economic value is proposed to sustain the creative kampung initiatives. It is because creative kampung provides a way to preserve culture and, at the same time, boost the local economy. Therefore, transforming slum villages in many cities into creative tourist villages is one of the solutions for dealing with urban slums.